The Influence Of Brand Relationship, Brand Satisfaction, And Perceived Price Towards Brand Loyalty In PT X’S Customer, Indonesia - Prihandoko, Danang (Bina Nusantara University, 2016)
The goal of this research was to examine the influence of Brand Relationship, Brand Satisfaction, and Perceived Price towards Brand Loyalty by using multiple regression analysis. This research was a combination of qualitative and quantitative studies where the results of the questionnaire would be summarized and described in the form of tables and graphs. The result shows the three hypothesis that Brand Relationship and Brand Satisfaction have a positive influence towards Brand Loyalty meanwhile Perceived Price does not have a positive influence or less effect towards Brand Loyalty to all PT X’s customer.